Electroacupuncture for treating depression-related insomnia: a systematic review and meta-analysis - Gao, Yu; Li, Tie; Lu, Qi; Wang, Jiaxin; Wang, Ying; Wang, Long (Frontiers in Psychiatry, 2025)
BackgroundDepression is a major mental disorder worldwide, affecting over 264 million people. Approximately 50% of individuals with depression also experience insomnia. The treatment of depression may be complicated by comorbid insomnia. Electroacupuncture (EA) has been widely used in clinical practice, with substantial empirical evidence accumulated for its role in treating both depression and related insomnia. However, a systematic evaluation of its efficacy is lacking. This study seeks to assess the efficacy and safety of EA for treating insomnia related to depression.MethodsWeb of Science, Sinomed, Cochrane Library, CNKI, Wanfang, Embase, and PubMed were searched up to November 2024 to select randomized controlled trials (RCTs) investigating EA for treating depression-related insomnia. The literature was selected and the data were extracted separately by two reviewers. The methodological quality of eligible RCTs was evaluated via the risk of bias 2 tool. Meta-analysis was carried out via Stata SE V.15.0 software.Results14 studies involving 1342 individuals with depression-related insomnia were included. The results unraveled that EA was more effective in reducing PSQI scores in comparison to the interventions used in the controls (WMD = -2.757, 95% CI: -3.759 to -1.755). Moreover, EA demonstrated superior efficacy in lowering HAMD scores in contrast to the interventions used in the controls (WMD = -3.587, 95% CI: -4.992 to -2.182). Regarding lowering PSQI scores, the subgroup analysis revealed that EA was more effective than Western medication (WMD =-3.598, 95%CI:-4.771 to -2.426), sham acupuncture (SA) (WMD = -3.623, 95% CI: -4.500 to -2.746). For reducing HAMD scores, the subgroup analysis demonstrated that EA had superior efficacy in comparison to Western medication (WMD =-4.903, 95%CI:-6.974 to -2.831), SA (WMD = -4.641, 95% CI: -6.913 to -2.369).ConclusionOur findings suggested that EA may be effective in treating depression-related insomnia. However, further large-scale, rigorously designed studies are required to validate its efficacy and safety.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023421281, identifier CRD42023421281.